FRET primers for quantitative real-time PCR: Optimization for genomic and cDNA templates - Ahmad, Ashraf I. (Research in Biotechnology, 2016)
Â  The chemistry of FRET (fluorescence resonance energy transfer) primers real-time thermal cycling technique depends on internally labeled primers with FRET dyes. Fluorescent dyes are linked internally close to the 3` end of both primers. FRET primers technique was tested and optimized on PCR products as an amplification template. It showed high efficiency, correlation coefficient and wide dynamic range in short amplification time. FRET primers technique was not tested on real sample materials such as genomic and cDNA. The main objective of this study was to test and optimize FRET primers on genomic and cDNA as an amplification templates to be used in research and diagnosis. Two steps amplification protocol (denaturation step and annealing-elongation step) showed higher efficiency, correlation coefficient and wider dynamic range compared to three steps protocol in case of genomic and cDNA templates. Moreover, shorter amplification time is needed for two steps protocol that makes FRET primers suitable and alternative choice for research and diagnostic purposes.Â 